ANTECEDENT CONTINUANCE RESIDENT COMMITMENT KOTA CIMAHI - Wulandari, Bela Amanda; Ernawadi, Yadi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This research aims to examine the influence of place image on the continuance resident commitment, which is mediated by resident satisfaction and place attachment among residents of Cimahi City. The cross-sectional or one-shot method was used to obtain data. The research instrument has been tested for validity and reliability through measurements of convergent validity, discriminant validity, and composite reliability. A total of 180 city residents living in Cimahi participated in this study. The data analysis technique used in this study was structural equation modeling (SEM) with the assistance of SmartPLS version 3.0. Out of nineteen proposed research hypotheses, twelve were supported by empirical data. The results of this study indicate that leisure and shopping facilities, social environment, and community services positively affect resident satisfaction. In contrast, physical appearance and ambient and community services positively impact place attachment. Resident satisfaction positively affects place attachment and continuance of resident commitment. In contrast, resident satisfaction mediates the effect of leisure and shopping facilities and community services on the continuance of resident commitment. Place attachment mediates the impact of physical appearance and ambient and community services on the continuance of resident commitment. In this study, the previous conceptual model was developed by testing the fourth dimension of place image, adding resident satisfaction as an intervening variable, and using continuance resident commitment as a dependent variable.